A remarkable sand-dwelling fish assemblage from central Amazonia, with comments on the evolution of psammophily in South American freshwater fishes - Zuanon, Jansen(Instituto Nacional de Pesquisas da Amazônia CPBA); Bockmann, Flávio A.(Universidade de São Paulo FFCLRP Departamento de Biologia); Sazima, Ivan(Universidade Estadual de Campinas Departamento de Zoologia and Museu de História Natural) (Neotropical Ichthyology, 2006)
We studied a specialised assemblage of sand-dwelling fish species from a streamlet in central Amazonia. The five sanddwelling species comprised 15.2 % of the total number in the streamlet (33 species). Two of the sand-dwellers are daytime foragers, Characidium cf. pteroides (Crenuchidae) and Stauroglanis gouldingi (Trichomycteridae), whereas three ones are night-time foragers, Gymnorhamphichthys rondoni (Rhamphichthyidae), "Imparfinis" pristos and Mastiglanis asopos (Heptapteridae). With the exception of C. cf. pteroides, the remainder species bury in the sand during their resting period. All five species bear a cryptic, sand-colour pattern, and some are translucent, traits which we regard as advantageous both for evasion from predators and for approaching prey (for the daytime foragers). All five species are microphagous carnivores and their foraging tactics range from generalised sit-and-wait (C. cf. pteroides) to active searching for interstitial prey (G. rondoni). A unique "drift-trap" system made up by the extended barbels and filamentous first pectoral-fin rays is employed by M. asopos. We regard the small size and low number of vertebrae (which is functionally expressed by fast displacements in the sand) as additional features advantageous to explore the sand habitat, allowing diving quickly in the substrate to evade predators and to forage for small prey in sand interstices or plant debris. The relationship between morphological and behavioural characters suited to life in sandy substrates is examined under the perspective of the current phylogenies for each group of psammophilous fishes here studied. The mapping of these characters demonstrates that not all of them evolved specifically for strict psammophily. Instead, some of them may represent the final step of a transformation series or synapomorphies of higher hierarchical levels. Several characters linked to psammophily, such as small body, large eyes, and scarce pigmentation are probably paedomorphic traits. We consider that the little variable specific composition of fish sand-dwelling assemblages and the wide (although patchy) geographical distribution of their species in the Amazon are due to the widespread occurrence and low complexity of this specialised habitat. The pre-existence of benthic habits, small size, and the broad distribution of rivers with sandy beds, mainly in the Amazon and Orinoco basins, possibly played a determinant role in the origin and diversification of psammophilous assemblages among freshwater fishes in South America. Estudamos uma comunidade especializada de espécies de peixes psamófilos de um igarapé na Amazônia central. As cinco espécies psamófilas correspondem a 15.2 % do número total estimado de espécies do igarapé (33 espécies). Duas das espécies psamófilas são forrageadores diurnos, Characidium cf. pteroides (Crenuchidae) e Stauroglanis gouldingi (Trichomycteridae), ao passo que três são forrageadores noturnos, Gymnorhamphichthys rondoni (Rhamphichthyidae), "Imparfinis" pristos e Mastiglanis asopos (Heptapteridae). Com exceção de C. cf. pteroides, as demais espécies ficam enterradas na areia durante seus períodos de repouso. Todas as cinco espécies apresentam padrão de colorido críptico na areia e algumas são translúcidas, características consideradas vantajosas tanto para evasão de predadores como para aproximação às presas (no caso dos forrageadores diurnos). Todas as espécies são carnívoras micrófagas e suas táticas de forrageamento variam de tocaia e espreita (C. cf. pteroides) a procura ativa de presas intersticiais (G. rondoni). Uma tática peculiar de caça ("armadilha-de-deriva"), com uso de barbilhões estendidos e primeiros raios da nadadeira peitoral filamentosos, é empregada por M. asopos. Consideramos que o tamanho pequeno e o baixo número de vértebras (funcionalmente expresso por deslocamentos rápidos) são caracteres adicionais vantajosos para explorar o hábitat arenoso, permitindo o enterramento rápido na areia para evadir dos predadores ou capturar as pequenas presas nos interstícios arenosos ou restos vegetais. As relações entre os caracteres morfológicos e comportamentais adequados à vida em substrato arenoso são analisadas sob a perspectiva das filogenias de cada grupo de peixes psamófilos aqui estudados. O mapeamento destes caracteres demonstra que nem todos evoluíram especificamente para a psamofilia estrita. Ao contrário, alguns podem representar o estágio final de uma série de transformação ou sinapomorfias de níveis hierárquicos mais elevados. Vários caracteres relacionados à psamofilia, como corpo pequeno, olhos grandes, pigmentação escassa, são provavelmente atributos pedomórficos. Consideramos que a composição específica pouco variável das comunidades psamófilas e a distribuição geográfica ampla de suas espécies (embora pontual) são devidas à estabilidade e à baixa complexidade deste hábitat especializado. A pré-existência de hábitos bentônicos, pequeno tamanho e a ampla distribuição de rios com leitos arenosos, principalmente nas bacias dos rios Amazonas e Orenoco, possivelmente tiveram um papel preponderante na origem e diversificação das assembléias de peixes psamófilos na ictiofauna de água doce da América do Sul.